A protein microarray assay for serological determination of antigen-specific antibody responses following Clostridium difficile infection - Negm, Ola H.; Hamed, Mohamed R.; Monaghan, Tanya M. (Journal of Visualized Experiments, 2018)
We provide a detailed overview of a novel high-throughput protein microarray assay for the determination of anti-C. difficile antibody levels in human sera and in separate preparations of polyclonal IVIg. The protocol describes the methodological steps involved in sample preparation, printing of arrays, assay procedure and data analysis. In addition, this protocol could be further developed to incorporate diverse clinical samples including plasma and cell culture supernatants. Herein, a combination of isotype (IgG, IgA IgM), subclass (IgG1, IgG2, IgG3, IgG4, IgA1, IgA2), and strain-specific antibodies to highly purified whole C. difficile toxins A and B (toxinotype 0, strain VPI 10463, ribotype 087), toxin B from a C. difficile toxin-B-only expressing strain (CCUG 20309), precursor form of B fragment of binary toxin, pCDTb, ribotype-specific whole surface layer proteins (SLPs; 001, 002, 027) and control proteins (Tetanus toxoid and Candida albicans) were determined by protein microarray. Microarrays were probed with sera from individuals with C. difficile infection (CDI), cystic fibrosis (CF) without diarrhea, healthy controls and individuals pre- and post-IVIg therapy for treatment of CDI, combined immunodeficiency disorder and chronic inflammatory demyelinating polyradiculopathy. Significant differences in toxin neutralization efficacies and multi-isotype specific antibody levels were seen between patient groups, commercial preparations of IVIg and sera before and following IVIg administration. A significant correlation was observed between microarray and enzyme-linked immunosorbent assay (ELISA) for antitoxin IgG levels in serum samples. These results suggest that microarray could become a promising tool for profiling antibody responses to C. difficile antigens in vaccinated or infected humans. With further refinement of antigen panels and a reduction in production costs, it is anticipated that microarray technology may help optimize and select the most clinically useful immunotherapies for C. difficile infection in a patient-specific manner.